Clinical and immunological features of rotavirus infection in children infected with herpesviruses - M.Yu. Sliepchenko; O.M. Olkhovska; Ya.V. Kolesnyk; A.V. Gavrylov (Український журнал Перинатологія і педіатрія)
The basis for conducting the study was the absence in the scientific literature of works devoted to the study of clinical and immunological features of rotavirus infection (RVI) in children against the background of the latent form of herpesvirus infection (lHVI) caused by cytomegalovirus (CMV) and human herpesvirus type 6 (HHV-6).